Sertraline Concentrations in Children Stratified by the CYP2C19 Genotype - France, Katelyn J (2020)
Biochemistry and Chemistry, Swenson College of Science and Engineering, UMD Off-label medication is commonly used in child and adolescent psychiatry, which raises concerns of both safety and efficacy, as common genetic variants of pharmacokinetic enzymes may significantly affect serum concentrations at a standard dosing level. Knowing an individual’s genotype, combined with trough serum levels, gives useful information to clinicians to help in determining an appropriate medication and dose. What remains unknown is what are the serum concentrations of psychiatric medications from standard dosing of sertraline in children with increased or decreased enzymatic activity. Therefore, there is an urgent need to define the range of serum concentrations for commonly used prescribed psychiatric medications frequently prescribed in children, such as sertraline. The purpose of this study is to [1] compare sertraline and desmethylsertraline concentrations and ratios in children (ages 6-17) taking sertraline (Zoloft) across different Cytochrome P450 2C19 (CYP2C19) genotype groups at a standard dosing level, to [2] assess clinical outcomes (including adverse drug events) across the different CYP2C19 metabolizer groups (poor, intermediate, normal, rapid or ultra-rapid), and [3] relate the results of this study to other pediatric pharmacogenetic studies of medication metabolization to synthesize novel conclusions about the pharmacogenetic differences between the chosen population (children and adolescents) and adults. University of Minnesota's Undergraduate Research Opportunities Program and Northwest Passage - Frederic, WI